1999
DOI: 10.1002/(sici)1097-010x(19990101)283:1<71::aid-jez8>3.3.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Deciliation in the ampulla of the rat oviduct and effects of estrogen on the process

Abstract: The mechanism by which cells in the ampullae of the rat oviducts undergo rapid deciliation during each estrous cycle and the effects of estrogen on the ciliated cells were examined. Untreated rats were killed on each day of the 5-day estrous cycle, and the ampullae of their oviducts were removed. Other rats were injected subcutaneously each day for 5 days with 0.3 microgram or 3.0 micrograms of estradiol benzoate or with 0.3 mg of tamoxifen, an estrogen antagonist, per kilogram of body weight. The ampullae of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 0 publications
1
12
0
1
Order By: Relevance
“…Large numbers of cilia in the oviduct are formed during the follicular phase by the pattern of cilia formation appearing as daisy-like structures (Dirksen 1974) and extensive atrophy and deciliation take place during the luteal phase (Brenner 1969). Moreover, Reeder and Shirley (1999) suggested that the ciliated cells in the ampulla deciliate rapidly by shedding their cilia in the lumen of the oviduct. Taken together with these finding and the SEM results in this study, the patterns of ciliogenesis or deciliation were not illustrated in the buffalo oviduct throughout the cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Large numbers of cilia in the oviduct are formed during the follicular phase by the pattern of cilia formation appearing as daisy-like structures (Dirksen 1974) and extensive atrophy and deciliation take place during the luteal phase (Brenner 1969). Moreover, Reeder and Shirley (1999) suggested that the ciliated cells in the ampulla deciliate rapidly by shedding their cilia in the lumen of the oviduct. Taken together with these finding and the SEM results in this study, the patterns of ciliogenesis or deciliation were not illustrated in the buffalo oviduct throughout the cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, change of cell phenotype from secretory to ciliated cells with estrogen treatment was demonstrated in primary culture of human oviductal epithelial cells (Comer et al 1998). Moreover, Reeder & Shirley (1999) suggested the possibility of transformation from ciliated cells to secretory cells following loss of cilia in an electron microscopic study. Further elucidation of this matter is necessary.…”
Section: Figurementioning
confidence: 99%
“…This strongly suggests that GPx-4 expression in the oviductal epithelium is regulated by a signal from the active ovary rather than in response to the presence of the oocyte. The mammalian oviduct is known to be under the influence of local steroids, especially the estrogens (61,62). The estrogens are known to induce the transcription of specific genes in the mammalian oviduct (1,(63)(64)(65).…”
Section: Discussionmentioning
confidence: 99%